2008
DOI: 10.1007/s11340-008-9198-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Impact Testing of Energy Dissipation at Surfaces

Abstract: Impact testing with nanoscale spatial, force, and temporal resolution has been developed to address quantitatively the response of surfaces to impingement of local contact at elevated velocities. Here, an impact is generated by imparting energy to a pendulum carrying an indenter, which then swings towards a specimen surface. The pendulum displacement as a function of time x(t) is recorded, from which one can extract the maximum material penetration x max , residual deformation x r , and indentation durations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 36 publications
(50 reference statements)
1
35
0
Order By: Relevance
“…The nano-impact (impulse indentation) technique in the NanoTest system can simulate the mechanical conditions occurring in contact and predict the wear performance of coated systems subjected to repetitive contact [2,[29][30][31][32]. In this test repetitive high strain rate impact indentation occurs at the same location on the sample surface and the evolution of film damage can be monitored in situ.…”
mentioning
confidence: 99%
“…The nano-impact (impulse indentation) technique in the NanoTest system can simulate the mechanical conditions occurring in contact and predict the wear performance of coated systems subjected to repetitive contact [2,[29][30][31][32]. In this test repetitive high strain rate impact indentation occurs at the same location on the sample surface and the evolution of film damage can be monitored in situ.…”
mentioning
confidence: 99%
“…Constantinides et. al has indicated that the for various loading conditions v in for the NanoTest TM system can range from 0.7 mm/s to 2.5 mm/s [38]. As the load was low in the current investigation, a lower value of 0.7 mm/s can be assumed as average to cover the loading range considered in this investigation.…”
Section: Nano-impact Analysismentioning
confidence: 80%
“…These instruments for example may be used to evaluate the damage analysis on solar panels during a sand storm with a typical sand particle velocity of 50 km/hr ≈ 1.4 × 10 4 mm/s. Although such velocity is not achievable by the indenting probes in either of the systems discussed above, there is difference in the mass of indenter (effective mass of pendulum and tip is 0.21 kg for the NanoTest TM system [37][38]) and the mass of typical sand particle (≈10 -5 kg to 10 -6 kg). This difference in mass can be used to compensate the lower impact velocity of nanoindentation system, and hence can impart the correct momentum and energy during the dynamic contact.…”
Section: Nano-impact Analysismentioning
confidence: 99%
“…Single impact experiments are typically used to determine the "dynamic hardness" of a sample [100][101]. This is the effective hardness of the material at a given rate of strain.…”
Section: Single Impact Testsmentioning
confidence: 99%
“…The dynamic hardness in this test was 8 GPa compared with around 5 GPa under quasi-static conditions. Constantinides and coworkers reported [101] that gold was even more sensitive to strain rate but aluminium was much less so ( …”
Section: Single Impact Testsmentioning
confidence: 99%